Surgical Outcome of Spine Tumor Surgery - Waheed Alam, Asghar Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim and objective: The aim of the study was to assess the outcome of spinal tumor surgery. Materials and Method: The current prospective study was conducted from June 2022 to July 2023 at Jinnah Teaching Hospital after approval from the institutional review board. A total of 72 patients were selected through a convenient sampling technique including both male and female. Every patient has had an MRI as well as an X-ray taken. The posterior midline technique was used in all surgical procedures. All the data were collected from physical records, histopathology, and lab reports and then analyzed by using the latest version of SPSS 24. Results: A total of 72 clients were selected for the current study aged from 10-75 years of age. 44.44 % of them were from 46-60 years and 40.27 % of them were from 61-75 years of age. 58.33 % of them were males and 41.66 % of them were females. 70.83 5% had pain and 15.27 % had motor impairments. 9.71 % had sensory and 4.16 % of them had sphincter impairments. 26.38 % had a muscular weakness. 33.33 % had schwannoma, 12.5 % had lipoma, 9.71 % had an arachnoid cyst and 23.61 % had a meningioma. 6.94 % had instant improvement, 27.77 % had improved after a week, 44.44 % had after a month, and 12.5 % of them had no improvements, furthermore, the rate of mortality was 2.7 %. The post-op complications like infection and leakage of CSF were 11.11 % and 4.16 % respectively. Conclusion: The current study concluded that early surgical interventions are necessary for the patients in order to or the best chance of a full and speedy recovery from both physiological and anatomical handicap caused by a spinal tumor, prompt surgical intervention and complete removal of the tumor are essential. Schwannoma 33.33 % was the most common histopathological finding. Keywords: Schwannoma, Spinal tumor, Cervicothoracic, CSF.